Fluid attenuated inversion recovery vascular hyperintensities possibly indicate slow arterial blood flow in vertebrobasilar dolichoectasia - Förster, Alex; Kerl, Hans Ulrich; Wenz, Holger; Mürle, Bettina; Habich, Sonia; Groden, Christoph (Journal of neuroimaging, 2015)
Background and purpose: Vertebrobasilar dolichoectasia (VBD) is a dilatative arteriopathy associated with a decreased blood flow velocity. Fluid attenuated inversion recovery (FLAIR) vascular hyperintensity (FVH) is a phenomenon most likely representing slow arterial blood flow. We sought to examine the frequency and extent of FVH in VBD. Methods: We analyzed magnetic resonance imaging (MRI) findings in 77 VBD patients with special emphasis on FVH in relation to the diagnostic MRI criteria of VBD and the etiology in symptomatic patients. Results: In 49 (63.6%) VBD patients, FVH could be detected: in 22 (44.9%) a small hyperintense rim near the vessel wall (grade 1), in 20 (40.8%) a strong hyperintense rim near the vessel wall (grade 2), and in 7 (14.3%) the hyperintense signal filled the complete vessel lumen (grade 3). The diameter of the basilar artery moderately correlated with the extent of FVH. A higher FVH grade (2 and 3) was more common in patients with TIA/stroke related to VBD (9/16 [56.3%]) in comparison to patients with other etiology and asymptomatic patients (18/61 [29.5%]; P = .046). Conclusions: FVH may be useful to demonstrate the decreased blood flow velocity in VBD. More pronounced FVH in patients with posterior circulation TIA/stroke might reflect the underlying stroke pathomechanism.